Is inter-firm labor mobility a channel of konwledge spillovers? Evidence from a linked employer-employee panel - Mika Maliranta; Pierre Mohnen; Petri Rouvinen (The Research Institute of the Finnish Economy (ETLA), 2008)
An employer-employee panel is used to study whether the movement of workers across firms is a channel of unintended diffusion of R&D-generated knowledge. Somewhat surprisingly, hiring workers from others' R&D labs to one's own does not seem to be a significant spillover channel. Hiring workers previously in R&D to one's non-R&D activities, however, boosts both productivity and profitability. This is interpreted as evidence that these workers transmit knowledge that can be readily copied and implemented without much additional R&D effort.
Keywords: D62; J24; J62; L25; O31; 330; Labor mobility; R&D spillovers; Profitability; Linked employer-employee data; Arbeitsmobilität; Betriebliche Forschung; Wissenstransfer; Theorie; Finnland